Regioselective control of the nickel-mediated coupling of acetylene and carbon dioxide - A DFT study - Graham, D.; Bruce, M.; Bowie, J.; Buntine, Mark (Elsevier, 2008)
The nickel-mediated coupling of asymmetric alkynes with carbon dioxide is known to be highly regioselective with respect to the formation of nickelacycle intermediates and α,β-unsaturated carboxylic acid products. Using density functional theory (DFT), we have investigated the effect that parameters such as acetylene-substituent, ancillary ligand and solvent have on the potential energy surface of the nickelacycle coupling reaction. 3-R-substituted nickelacycles are the thermodynamically preferred product in all cases surveyed, however, the transition structure characterised by the attack of CO2 on the alkyne carbon distal from the R-group is generally lower in energy, making the 2-R-substituted nickelacycle the kinetically favoured product. Ligating the zerovalent nickel species with the diazabicyclo[5.4.0]undec-7-ene (DBU) ancillary ligand in preference to 2,2′-bipyridine (BIPY) leads to lower activation energies for the coupling reaction and products that are less susceptible to steric bulk in the 2-position of the nickelacycle. Solvation with dimethylformamide (DMF) has the advantage of lowering the activation barrier for the coupling reaction when compared to tetrahydrofuran (THF).